Mapeamento do risco sanitário e associação com indicadores socioeconômicos no Programa Nacional de Alimentação Escolar do estado de Sergipe - Canuto, Isabela Gomes (2024)
The National School Feeding Program is a tool of great importance on guaranteeing Brazilian’s Food and Nutrition Security, being one of the ways to assure the Human Right to Adequate and Healthy Food for the assisted population. The compliance of this right cannot be compromised by any other system violation, therefore, indissociable. So, a possible association between the sanitary quality of the food provided and the socioeconomic profile in the location where the schools belong would characterize a human right violation. Thus, this study aimed to associate the food safety in public state schools of Sergipe with the respective socioeconomic indicators of the municipalities they were held. It was also aimed being a pioneer in diagnosing the National School Feeding Program in a state level and using geographic mapping to represent the results. To do that, the food safety data of all the 314 public state schools were provided by the Educational and Culture State Department of Sergipe. The socioeconomic data were obtained through the Brazilian Institute of Geography and Statistics’ database and the Social Vulnerability Atlas. Cluster analysis was applied to verify the association between socioeconomic indicators and food safety in schools. To construct the maps, the software GeoDa was used. Additionally, this work was financed by the Research and Technological Innovation Support Foundation of the state of Sergipe. The application of those methods resulted in two clearly defined clusters, with significant levels (p<0.05) for most of the variables assessed. Cluster 1 had the worse socioeconomic profile and worse general scores of food safety, whereas cluster 2 presented better results. This indicates the compromising of food quality offered by schools according to the socioeconomic profile of their location, which characterizes a Human Right to Adequate and Healthy Food violation in the National School Feeding Program of Sergipe.